Arah Baru Pendidikan Islam Di Sekolah Pada Era Kenormalan Baru - Syaiful, Muhammad; Sayyi, Ach; Rosyid, Moh Zaiful (TADRIS: Jurnal Pendidikan Islam, 2021)
Islamic education in the new normal era has at least given new hope, namely the implementation of education that is better than before. The learning system carried out during the pandemic has made us aware of the importance of innovation in the realm of education. This innovation was carried out in order to respond to social changes after Covid-19 and to face the all-digital industrial era 4.0. The changes made are by applying the concept of Merdeka Belajar which in general has several points, namely: 1) the replacement of the National Examination System with the AKM, the application of one page lesson plans, activating organizations, activating schools, activating teachers, and emergency curriculum.